2015
DOI: 10.1186/s12896-015-0203-3
|View full text |Cite
|
Sign up to set email alerts
|

Construction of polyomavirus-derived pseudotype virus-like particles displaying a functionally active neutralizing antibody against hepatitis B virus surface antigen

Abstract: BackgroundVirus-like particles (VLPs) can be efficiently produced by heterologous expression of viral structural proteins in yeast. Due to their repetitive structure, VLPs are extensively used for protein engineering and generation of chimeric VLPs with inserted foreign epitopes. Hamster polyomavirus VP1 represents a promising epitope carrier. However, insertion of large sized protein sequences may interfere with its self-assembly competence. The co-expression of polyomavirus capsid protein VP1 with minor caps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…Moreover, hamster polyomavirus VLPs comprising native VP1 and chimeric VP2 harbouring an anti‐HBsAg antibody molecule have been produced in S. cerevisiae , and they allowed surface exposure of functionally active neutralizing antibody against HBsAgs (Pleckaityte et al . ).…”
Section: Yeast‐derived Vlps As Delivery Systems For Antigens Nucleicmentioning
confidence: 97%
“…Moreover, hamster polyomavirus VLPs comprising native VP1 and chimeric VP2 harbouring an anti‐HBsAg antibody molecule have been produced in S. cerevisiae , and they allowed surface exposure of functionally active neutralizing antibody against HBsAgs (Pleckaityte et al . ).…”
Section: Yeast‐derived Vlps As Delivery Systems For Antigens Nucleicmentioning
confidence: 97%
“…There exists another approach to designing therapeutic vaccines based on VLPs. In this case, the VLP surface displays the variable fragment of an antibody specific to the antigen of the target virus [65]. Moreover, knowing which receptor is bound by the virus proteins renders it possible to produce particles possessing tropism to the cells of certain tissues.…”
Section: Recombinant Vlps For Presentation Of Foreign Antigenic Determentioning
confidence: 99%
“…GFP was fused to the C-terminus of VP2C and was tagged with 6His to enable purification. Unlike previous reports where GFP was fused to the N-terminus of MPyV VP2 (Abbing et al 2004;Boura et al 2005), in my research GFP was fused to C-terminus of VP2C based on the findings of Inoue et al (2008) with SV40 andPleckaityte et al (2015) with HPyV, that suggested a complete encapsidation with C-terminal fusion.…”
Section: Optimisation Of Encapsidationmentioning
confidence: 90%
“…Fusion at the C-terminus of VP2C is expected to position GFP inside the cavity of the VLP (Inoue et al 2008;Pleckaityte et al 2015). This attempt was done by two approaches, the first is to bind VP2C-GFP and VP1 capsomeres in vitro, and the second is to facilitate binding of VP2C-GFP and VP1 capsomeres in vivo.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation